Effects of recombinant human prothrombin on thrombin generation in plasma from patients with hemophilia A and B. (8th June 2015) - Hansson, K. M.; Gustafsson, D.; Skärby, T.; Frison, L.; Berntorp, E.
Summary Background The present study was carried out to investigate the impact of FII levels, and their increase, on the hemostatic potential in plasma from hemophilia A and B patients with and without inhibitors. Method Recombinant human factor (F) II (rhFII) was added ex vivo to plasma from 68 patients with hemophilia A and B, with or without inhibitors. The hemostatic potential as measured by thrombin generation (calibrated automated thrombogram [CAT]) was focused on the endogenous thrombin potential (ETP) as it has been shown to correlate with the clinical phenotype of bleeding in hemophilia patients and has also been used to guide bypassing therapy in hemophilia patients with inhibitors before elective surgery. The factor eight inhibitor bypassing agent (FEIBA®) was used as a reference to the clinical situation. Results The study shows that rhFII concentration‐dependently increased ETP by a similar magnitude in hemophilia A and B, both with and without inhibitors. Compared with FEIBA, rhFII showed a shallower concentration‐response curve. In both types of hemophilia 100 mg L−1 of rhFII roughly doubled the ETP. A corresponding response was obtained by 0.5 U mL−1 of FEIBA. Conclusion These data support the theory that FII is one of the major components responsible for the efficacy of FEIBA. The data also indicate that rhFII may be useful, alone or in combination with other coagulation factors, in some of the conditions for which FEIBA is used today, although more data are needed to substantiate this.